2005
DOI: 10.1074/jbc.m500871200
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a Surface Hydrophobic Pocket on Protein Phosphatase-1 Catalytic Subunit in Recognizing Cellular Regulators

Abstract: Cellular functions of protein phosphatase-1 (PP1), a major eukaryotic serine/threonine phosphatase, are defined by the association of PP1 catalytic subunits with endogenous protein inhibitors and regulatory subunits. Many PP1 regulators share a consensus RVXF motif, which docks within a hydrophobic pocket on the surface of the PP1 catalytic subunit. Although these regulatory proteins also possess additional PP1-binding sites, mutations of the RVXF sequence established a key role of this PP1-binding sequence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Despite the apparent dissimilarity between Gln and Val, the aliphatic C ␤ and C ␥ atoms of I-2 Gln 46 interact with PP1c similarly to Val, and most importantly, the side chain amide nitrogen of I-2 Gln 46 hydrogen bonds with the sulfhydryl of PP1c Cys 291 (Fig. 4d), which is highly conserved in all PP1c isoforms (45) and may contribute to the ability of I-2 to potently inhibit all PP1 catalytic subunits. In contrast, the equivalent position in PP2A is Tyr 284 , and this substitution as well as others in and around the corresponding binding site for residues 12-17 of I-2 accounts for the inability of I-2 to inhibit PP2A activity, despite the highly conserved active site structures in the PP1 and PP2A phosphatases (31,32).…”
Section: Structure Of the Pp1⅐inhibitor-2 Complexmentioning
confidence: 99%
“…Despite the apparent dissimilarity between Gln and Val, the aliphatic C ␤ and C ␥ atoms of I-2 Gln 46 interact with PP1c similarly to Val, and most importantly, the side chain amide nitrogen of I-2 Gln 46 hydrogen bonds with the sulfhydryl of PP1c Cys 291 (Fig. 4d), which is highly conserved in all PP1c isoforms (45) and may contribute to the ability of I-2 to potently inhibit all PP1 catalytic subunits. In contrast, the equivalent position in PP2A is Tyr 284 , and this substitution as well as others in and around the corresponding binding site for residues 12-17 of I-2 accounts for the inability of I-2 to inhibit PP2A activity, despite the highly conserved active site structures in the PP1 and PP2A phosphatases (31,32).…”
Section: Structure Of the Pp1⅐inhibitor-2 Complexmentioning
confidence: 99%
“…PP1 Catalytic Subunits-Recombinant PP1 catalytic subunits were expressed in E. coli as described (26). Native PP1 catalytic subunits were purified from rabbit skeletal muscle (27).…”
Section: Methodsmentioning
confidence: 99%
“…5B). While tPP1␣ has increased phosphatase activity, essentially normal RVXF binding (19), and normal subcellular localization (not shown), the inability to negatively regulate MEF2 suggests the far C terminus of PP1␣ is required for regulation of MEF2-dependent transcriptional activity. Since the C terminus of PP1 contains an important regulatory threonine residue (T320), we examined PP1␣ mutants that are constitutively active (threonine 320 mutated to alanine [T320A]) (2) or a phospho-mimetic, inactive phosphatase (T320 mutated to glutamic acid [T320E]) (Fig.…”
Section: Pp1␣ Interacts Directly With Mef2 Transcription Factorsmentioning
confidence: 99%
“…The three PP1 forms (␣, ␤, and ␥) show tissue-specific expression patterns and R-subunit binding specificity (11), and the necessary regions of PP1␣ involved in R-subunit interaction have been well characterized (19). Coexpression of PP1 [tPP1␣]) demonstrated that all three PP1 isoforms repress MEF2 transactivation activity, whereas tPP1␣ exerted no effect (Fig.…”
Section: Pp1␣ Interacts Directly With Mef2 Transcription Factorsmentioning
confidence: 99%